Phylogenetic analysis of host–symbiont specificity and codivergence in bioluminescent symbioses - Paul V. Dunlap; Jennifer C. Ast; Seishi Kimura; Atsushi Fukui; Tetsuo Yoshino; Hiromitsu Endo (2007)
Abstract Several groups of marine fishes and squids form mutualistic bioluminescent symbioses with luminous bacteria. The dependence of the animal on its symbiont for light production, the animal's specialized anatomical adaptations for harboring bacteria and controlling light emission, and the host family bacterial species specificity characteristic of these associations suggest that bioluminescent symbioses are tightly coupled associations that might involve coevolutionary interactions. Consistent with this possibility, evidence of parallel cladogenesis has been reported for squid–bacterial associations. However, genetic adaptations in the bacteria necessary for and specific to symbiosis have not been identified, and unlike obligate endosymbiotic associations in which the bacteria are transferred vertically, bacterially bioluminescent hosts acquire their light‐organ symbionts from the environment with each new host generation. These contrasting observations led us to test the hypotheses of species specificity and codivergence in bioluminescent symbioses, using an extensive sampling of naturally formed associations. Thirty‐five species of fish in seven teleost families (Chlorophthalmidae, Macrouridae, Moridae, Trachichthyidae, Monocentridae, Acropomatidae, Leiognathidae) and their light‐organ bacteria were examined. Phylogenetic analysis of a taxonomically broad sampling of associations was based on mitochondrial 16S rRNA and cytochrome oxidase I gene sequences for the fish and on recA , gyrB and luxA sequences for bacteria isolated from the light organs of these specimens. In a fine‐scale test focused on Leiognathidae, phylogenetic analysis was based also on histone H3 subunit and 28S rRNA gene sequences for the fish and on gyrB , luxA , luxB , luxF and luxE sequences for the bacteria. Deep divergences were revealed among the fishes, and clear resolution was obtained between clades of the bacteria. In several associations, bacterial species identities contradicted strict host family bacterial species specificity. Furthermore, the fish and bacterial phylogenies exhibited no meaningful topological congruence; evolutionary divergence of host fishes was not matched by a similar pattern of diversification in the symbiotic bacteria. Re‐analysis of data reported for squids and their luminous bacteria also revealed no convincing evidence of codivergence. These results refute the hypothesis of strict host family bacterial species specificity and the hypothesis of codivergence in bioluminescent symbioses. © The Willi Hennig Society 2007.